2019
DOI: 10.21106/ijma.277
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Plans And Utilization of Contraceptives Among Women Living With HIV

Abstract: Background: Despite public health policies aimed at providing universal access to reproductive health care services, the reproductive health needs of women living with Human Immunodeficiency Virus (WLHIV) are not adequately met. This study assesses the reproductive plans and utilization of contraceptives among WLHIV. Methods: This was a cross sectional descriptive study, which adopted a mixed method approach. A total of 400 respondents were recruited from two tertiary health institutions in Nigeria using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…I will not become pregnant as long as there are those injections and condoms” (Muthelo et al, 2020 ). This is corroborated in a study by Adeleye et al where the study findings revealed a significant association between knowledge level of contraceptive options and utilization of contraceptives and level of education and utilization of contraceptives among WLHIV (Adeleye et al, 2019 ).…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…I will not become pregnant as long as there are those injections and condoms” (Muthelo et al, 2020 ). This is corroborated in a study by Adeleye et al where the study findings revealed a significant association between knowledge level of contraceptive options and utilization of contraceptives and level of education and utilization of contraceptives among WLHIV (Adeleye et al, 2019 ).…”
Section: Resultssupporting
confidence: 77%
“…Studies conducted by Okawa et al revealed that 87.4% of study participants who were adolescents living with HIV desired to have children and most of these adolescents who expressed the desire to have children opined that they felt that having children has an important meaning in their adulthood (Okawa et al, 2018 ). This was corroborated by the findings of Adeleye et al ( 2019 )), Wagner et al ( 2021 )), Toska et al ( 2020 )), Arikawa et al ( 2020 )), and Mekonnen and Enquselassie ( 2017 )); all showing that WLHIV had a good desire to have children and that will influence their decision to get pregnant.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations